Intracortical inhibiton assessment using threshold tracking technique in amyotrophic lateral sclerosis - I. S. Bakulin; A. Kh. Zabirova; A. G. Poydasheva; D. O. Sinitsyn; D. Yu. Lagoda; A. R. Nagieva; M. N. Zakharova; N. A. Suponeva; M. A. Piradov (Нервно-мышечные болезни)
Background. Assessment of short-interval intracortical inhibition (SICI) using paired-pulse transcranial magnetic stimulation (TMS) and the threshold tracking technique is a promising approach to develop biomarkers of motor cortex damage in amyotrophic lateral sclerosis (ALS). Both high sensitivity and specificity of this approach were shown previously; however, almost all studies in this field were conducted by one group of authors.Aim. The replication of data showing impairment of SICI assessed by threshold tracking technique in patients with ALS.Materials and methods. 18 patients with ALS and 13 healthy volunteers were included into the study. Functional state of the patients was assessed as well as disease duration, form, stage and progression rate. Following values were determined in all participants using TMS: 1) resting motor threshold (MT); 2) mean motor evoked potential (MEP) amplitude of 30 stimuli applied with an intensity of 120 % MT; 3) SICI assessed using an algorithm based on paralleled optimized threshold tracking with interstimulus interval (ISI) of 1.0 ms, 1.5 ms, 2.0 ms, 2.5 ms, 3.0 ms, 3.5 ms, 4.0 ms, 5.0 ms, 7.0 ms, as well as mean inhibition for values with ISI from 1.0 to 3.0 ms and from 1.0 to 7.0 ms.Results. No significant differences between groups were observed for MT and MEP amplitude. Significant decrease of SICI with ISI 1.0 and 2.0 ms as well as mean SICI from 1.0 and 3.0 ms was observed in ALS. No significant correlations of MT, MEP amplitude or SICI with clinical values were found.Conclusion. This replication study has shown the ability of paired-pulse TMS with threshold tracking technique to identify the impairment of intracortical inhibition in patients with ALS.